An evidence-based guide to the selection of sequential therapies in metastatic renal cell carcinoma. (April 2013) - Sun, Maxine; Shariat, Shahrokh F.; Trinh, Quoc-Dien; Meskawi, Malek; Bianchi, Marco; Hansen, Jens; Abdollah, Firas; Perrotte, Paul; Karakiewicz, Pierre I.
Targeted therapies have introduced a paradigm shift in the management of metastatic renal cell carcinoma. Currently, four molecules (sunitinib, pazopanib, bevacizumab plus interferon, temsirolimus) are considered in first-line therapy, and three other molecules for second, or subsequent lines of therapy (everolimus, axitinib, sorafenib). In addition, other molecules and sequencing schemes are being tested in ongoing phase II/III studies. We conducted a systematic review using PubMed and several other databases up to December 2011 of prospective and retrospective studies on treatment management of metastatic renal cell carcinoma using targeted therapies, with a special focus on use of sequential treatment. Based on phase III data, the optimal sequencing scheme for patients with clear cell or even non-clear cell histological subtype appears to consist of sunitinib, followed by axitinib, followed by everolimus. Subsequent treatment options rely on lower evidence studies and could consist of fourth-line sorafenib or sunitinib rechallenge. Such therapies would qualify as last recourse options. In another context, temsirolimus may be used in patients who fulfill the Memorial Sloan-Kettering Cancer Center poor risk criteria or who have poor performance status. We conclude that in the current setting, sequential therapy represents the cornerstone of effective management of metastatic renal cell carcinoma.